THE USE OF ICTS IN ADAPTING ACTIVITIES FOR TEACHING MATHEMATICS IN ADULT EDUCATION (HIGH SCHOOL LEVEL) - Andrade, Sandro Gomes; Bezerra, Francisco Damião (Seven Editora, 2026)
This study addresses the use of Digital Information and Communication Technologies (DICTs) in mathematics education within Youth and Adult Education (YAE), a modality characterized by interrupted school trajectories, sociocultural diversity, and historical learning challenges. The objective was to investigate how DICTs have been used to adapt mathematical activities for YAE high school students, analyzing theoretical productions, teaching materials, and educational documents. Methodologically, it is a bibliographic and documentary research, with a qualitative approach and a pedagogical-propositional character, organized through analytical categories that enabled a critical interpretation of the findings. Results indicate that DICTs, when integrated into pedagogical proposals planned and critically mediated by teachers, can enhance the visualization of mathematical concepts (C1), increase student engagement through gamification (C2), and promote more meaningful and contextualized learning experiences (C3). The analysis also highlights limitations related to precarious technological infrastructure, digital access inequalities, and gaps in teacher training (C4). It is concluded that the integration of DICTs into mathematics teaching in YAE represents a promising path for building more inclusive and contextualized pedagogical practices, provided it is articulated with teacher training policies and digital inclusion initiatives. The main contribution of this research lies in the articulation between theoretical analysis and pedagogical proposition, by presenting a set of didactic activities adapted with DICTs, offering concrete support for teachers and researchers interested in more critical, inclusive, and transformative practices in mathematics education within YAE.